The effect of process variables on the physical properties and microstructure of HOPO nanoemulsion flakes obtained by refractance window - M. Hernández-Carrión (Nature Portfolio, 2021)
Abstract Refractance window (RW) drying is considered an emerging technique in the food field due to its scalability, energy efficiency, cost and end-product quality. It can be used for obtaining flakes from high-oleic palm oil (HOPO) nanoemulsions containing a high concentration of temperature-sensitive active compounds. This work was thus aimed at studying the effect of temperature, thickness of the film drying, nanoemulsion process conditions, and emulsion formulation on the flakes’ physical properties and microstructure. The results showed that HOPO flakes had good physical characteristics: 1.4% to 5.6% moisture content and 0.26 to 0.58 aw. Regarding microstructure, lower fractal dimension (FDt) was obtained when RW drying temperature increased, which is related to more regular surfaces. The results indicated that flakes with optimal physical properties can be obtained by RW drying of HOPO nanoemulsions.